Government and voluntary policymaking for sustainability in mining towns: A longitudinal analysis of Itabira, Brazil. (11th July 2013) - Fonseca, Alberto; Fitzpatrick, Patricia; McAllister, Mary Louise
Abstract The socio‐economic fabric of single‐company mining towns needs to be carefully considered by both Government and companies in sustainability policymaking. Policy design and effectiveness in such towns are significantly impacted by the city's economic dependence on a single company. This paper explores the perceived effectiveness of government and voluntary private sector mining policies for pursuing sustainability in the historic mining town of Itabira, Brazil over a period of 20 years. Itabira serves as a worthwhile case study because it allows for an in‐depth and longitudinal analysis that can reveal valuable lessons to policymakers of different sectors and jurisdictions located elsewhere. Based on extensive face‐to‐face interviews and literature reviews, study results indicate that changes to the state environmental licensing policies in the 1990s led to significant socio‐environmental improvements in the area. The globalization of the mining company also contributed to an increase in the quantity and quality of voluntary industry policies. Recent technological improvements in the beneficiation processes of the mining company promises to extend the life of the mine to 2050. Although there are significant incremental socio‐environmental policies and programmes, sustainability remains an elusive vision in Itabira, with no clear objectives or monitoring and accountability mechanisms. The paper concludes by recommending a more formal integrated policymaking framework.